US Bipartisan Consensus on China: The Making and the Implementation - V. Yu. Zhuravleva (Сравнительная политика)
According to the most experts, there is a bipartisan consensus in the United States regarding China: both parties recognize that China poses an existential threat to the United States, its economy, socio-political structure and the role as a global leader. This core conceptual consent represents a clear contrast with the endless battles between Democrats and Republicans in the domestic political arena, blocking any legislative initiatives and the development of a unified sociopolitical agenda for the country. This rare unity has made many observers to claim the emergence of a new external enemy, in the face of which America will be able to overcome its identical crisis and to come back to national unity. The political elite also actively uses the image of the enemy, calling on the Nation for unity. This article is aimed to understand what lies behind political slogans and the bipartisan concept of confronting China. The study is based on the analysis of several sources that make it possible to judge the attitude towards China in the United States along party lines, specific to each level of the party-political system party platforms at the federal level, legislative initiatives at the state and city levels, public opinion polls at the level of the society. The research hypothesis is that Democrats and Republicans, who agree on the conceptual vision of the Chinese threat, offer different ways to counter it. The difference in methods of struggle stems from different ideological and value models that manifest themselves in the implementation of both the socioeconomic agenda within the country and foreign policy strategies in the international arena. The unity of the parties ends exactly by the developing of a conceptual framework for confrontation with the opponent. The implementation of specific steps of the anti-Chinese agenda at the state and city levels is taking place in accordance with the ideological and political guidelines of each party, and the public attitude towards the Chinese threat demonstrates a clear split along party lines. The conceptual positioning of a new external enemy instead of unification brought to the United States anti-Chinese hysteria among conservative politicians at the state level, which was realized in the adoption of discriminatory laws in Republican states against Chinese citizens and a new wave of anti-Chinese sentiment in society, manifested in outbreaks of violence against Asian minorities.